Situación de los adultos mayores con enfermedades catastróficas como obligados subsidiarios en los casos de reclamación de alimentos. - Chaguaro Coloma Gardenia Lizbeth (2024)
Through this research work entitled “SITUATION OF OLDER ADULTS WITH CATASTROPHIC ILLNESSES AS SUBSIDIARY OBLIGATORS IN FOOD CLAIM CASES”, an exhaustive analysis will be carried out from the legal and social perspective of the problems faced by older adults. when, despite their own difficulties and limitations, they are considered subsidiary responsible for food claims. Therefore, this research will focus on understanding the urgency of taking into account their current situation, covering economic, biological, physical and emotional aspects, and how all these aspects become a problem that worsens when they go through a catastrophic illness. Nowadays older adults face many difficulties; since socially, they are often marginalized in various aspects; Many do not receive a retirement pension because they dedicated their lives to jobs such as crafts or agriculture, without joining social security. It must be noted that aging brings with it inevitable aches and pains, but it is even more worrying when elderly people also deal with catastrophic illnesses; since, suffering from these require expensive treatments that in many cases must be financed on their own, since the state health system does not always respond adequately to the needs of citizens (López, 2020). As provided in the Organic Code of Children and Adolescents (CONA), older adults may be responsible for paying the support of children and adolescents when the main obligors are absent and when they do not have the resources to pay. his minimum maintenance; This constitutes a big problem because their health conditions are not taken into consideration and their rights are ignored. Here lies the relevance of this research work, 6 seeking to determine from the basis of law to what extent rights are violated and what type of legal protection this vulnerable group, such as older adults with catastrophic illnesses, really have; Thus, to carry out this analysis, the doctrine was examined from the perspective of the rights of vulnerable groups, placing special emphasis on older adults and those with catastrophic illnesses (Naranjo, 2009). We will use a methodology that includes deductive, inductive, analytical and exegetical approaches. We will rely on field research tools such as interviews and surveys applied to a relevant population group to obtain data that complement our study. The final objective is to propose specific legal recommendations that protect the rights and dignity of older adults who also have a situation of suffering from a catastrophic illness. This research highlights the urgent need to review and modify the laws that force older adults to be subsidiary responsible in cases of alimony, especially when they face serious or catastrophic illnesses. Framing as one of the important points to be addressed in this legal problem is the search to guarantee that the rights of these groups are protected and therefore their dignity assured and respected, thus it is proposed to make legislative changes that reflect a deeper understanding of their situation and needs, seeking coherent and logical solutions that attribute to well-being and vulnerability. The qualitative research methodology, with the dogmatic and interpretive method of the constitutional and legal norm, since through these methods an answer to the problem treated is offered based on what is believed to be the best possible reconstruction allowed by the legal material. that you have at your disposal; In addition, the facts or social phenomena studied in this work are measurable and quantifiable. I will measure and 7 establish causal relationships between the variables, to explain the problem of study and the current social reality. Keywords: older adults, catastrophic illnesses, subsidiary obligors, claim for maintenance, legal protection.